2011
DOI: 10.1111/j.1574-6941.2011.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ identification of keratin-hydrolyzing organisms in swine manure inoculated anaerobic digesters

Abstract: Feathers, a poultry byproduct, are composed of > 90% keratin which is resistant to degradation during anaerobic digestion. In this study, four 42-L anaerobic digesters inoculated with adapted swine manure were used to investigate feather digestion. Ground feathers were added into two anaerobic digesters for biogas production, whereas another two without feathers were used as negative control. Feather degradation and enhanced methane production were recorded. Keratin-hydrolyzing organisms (KHOs) were visualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Changes in the number of active microbial groups in digesters were characterized using fluorescent rRNA-targeted oligonucleotide probes specific to phylogenetically defined groups of selected bacteria (Gammaproteobacteria and Firmicutes) and methanogens (Methanobacteriales and Methanosarcinales), according to the most abundant groups of microorganisms detected in manure digesters. 14,15,29,37,38 The vitality of Gammaproteobacteria and Firmicutes were investigated in acidogenic digesters and compared with single-phase digesters. Similarly, the vitality of Methanobacteriales and Methanosarcinales were investigated in methanogenic digesters and compared with single-phase digesters.…”
Section: Fish Resultsmentioning
confidence: 99%
“…Changes in the number of active microbial groups in digesters were characterized using fluorescent rRNA-targeted oligonucleotide probes specific to phylogenetically defined groups of selected bacteria (Gammaproteobacteria and Firmicutes) and methanogens (Methanobacteriales and Methanosarcinales), according to the most abundant groups of microorganisms detected in manure digesters. 14,15,29,37,38 The vitality of Gammaproteobacteria and Firmicutes were investigated in acidogenic digesters and compared with single-phase digesters. Similarly, the vitality of Methanobacteriales and Methanosarcinales were investigated in methanogenic digesters and compared with single-phase digesters.…”
Section: Fish Resultsmentioning
confidence: 99%
“…BODIPY FL DQ TM casein staining was performed as previously described for biodigester sludge by Xia et al (2011) with slight modifications. Briefly, 400 µL of filtrated bag fluids were transferred into 1.5-mL Eppendorf tubes and centrifuged (4500 g for 10 min).…”
mentioning
confidence: 99%
“…1A). BODIPY FL DQ TM casein staining combined with DAPI (4′,6-diamidino-2-phenylindole; Xia et al 2011) showed that these PHOs were more abundant (5-10% of total microbial cells) in the low concentrate than in the high concentrate diet (3-6% of total microbial cells), suggesting that they played a more important role in proteolysis of the low concentrate diet. We used BODIPY FL DQ TM casein staining combined with FISH (Xia et al 2007) to identify PHOs with CSA serine-and metallo-protease activity.…”
mentioning
confidence: 99%
“…Clone SPAD53 was retrieved from a keratin (recalcitrant organic material) digestion system. In the system of Xia [ 51 ], a TAN concentration of 5.5–7.5 g/L was beneficial to the SAO pathway. However, it was difficult to precisely identify the family and genus categories of both Bac-OTU-17 and Bac-OTU-21 due to the lack of cultured relatives.…”
Section: Resultsmentioning
confidence: 99%